Self-Esteem as a Mediating Mechanism in the Association Between Emotional Experiences and Academic Performance in School Students: The Moderating Role of Age - Roxana Bernal-Rojas; David Quispe-Sanca; Gutember Peralta-Eugenio; Wilter C. Morales-García; Liset Z. Sairitupa-Sanchez (European Journal of Investigation in Health, Psychology and Education, 2026)
Background: Academic performance does not depend solely on cognitive abilities, but also depends on socioemotional processes. Emotional experiences may be associated with school performance; however, their effects are often inconsistent, suggesting the need to examine mediating mechanisms such as self-esteem and developmental conditions such as age. Objective: We aimed to analyze the association between positive and negative emotional experiences and academic performance in school students, assessing the mediating role of self-esteem and the moderating effect of age. Methods: A cross-sectional explanatory study was conducted with 325 students from Lima, Peru (149 boys and 176 girls). Emotional experiences were assessed using the PANAS-N, self-esteem with the Rosenberg Self-Esteem Scale, and academic performance with final grades in Communication and Mathematics. Data were analyzed using partial least squares structural equation modeling (PLS-SEM), with bootstrapping based on 10,000 subsamples. Results: Positive emotional experiences were positively associated with self-esteem (β = 0.434, p < 0.001) and academic performance (β = 0.272, p < 0.001). Negative emotional experiences were negatively associated with self-esteem (β = −0.489, p < 0.001) but showed no significant direct association with academic performance (β = −0.005, p > 0.05). Self-esteem was positively associated with academic performance (β = 0.114, p = 0.043). The model explained 40.8% of the variance in self-esteem and 11.3% of the variance in academic performance. Age moderated only the association between negative emotional experiences and self-esteem (Δβ = 0.183, p = 0.035). Conclusions: Self-esteem plays a significant mediating role in the association between emotional experiences and academic performance, and this effect is especially relevant during adolescence. The findings suggest that self-worth constitutes a key psychological process for understanding how emotional experiences are linked to school performance.